Angular correlation α-particles in the reaction ¹²С(γ, 3α) at the formation of ⁸Be nucleus in the first excited state - Afanas’ev, S.N. (Вопросы атомной науки и техники, 2011)
Investigation of channel formation of the first excited state of ⁸Be nucleus in ¹²С(γ, 3α) reactions is executed. The methodic of kinematical models of γ + ¹²С → α₁ + ⁸Be* reaction is developed and is correctly selected α₁-particle. The angular distributions of γ + ¹²С → α₁ + ⁸Be* reaction and channel of disintegration of nucleus ⁸Be* → α₂ + α₃ are measured. The elements of density matrix of ⁸Be* nucleus and spherical spin-tensors characterizing polarization of ⁸Be* nucleus definite.